1995
DOI: 10.1093/nar/23.18.3673
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the yeast nuclear gene for the mitochondrial homologue of bacterial ribosomal protein L16

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…We named it YmL47 and searched for the gene that could code for the two sequences. We consequently found the gene for YmL47 which was in fact identical to the gene encoding protein Rmll6p reported by Pan and Mason [15]. A nucleotide sequence capable of encoding the N-terminal 38 residues of protein YniL1.5 was found to be present between ORFs YLR312c and YLR313c on chromosome XI1 (Table 3).…”
Section: Resultssupporting
confidence: 76%
“…We named it YmL47 and searched for the gene that could code for the two sequences. We consequently found the gene for YmL47 which was in fact identical to the gene encoding protein Rmll6p reported by Pan and Mason [15]. A nucleotide sequence capable of encoding the N-terminal 38 residues of protein YniL1.5 was found to be present between ORFs YLR312c and YLR313c on chromosome XI1 (Table 3).…”
Section: Resultssupporting
confidence: 76%
“…These genes include those encoding mitochondrial ribosomal proteins; assembly factors; components of the respiratory complexes; proteins required for import, stabilization, and processing of cytoplasmically synthesized mitochondrial proteins; and known and putative members of the family of mitochondrial carrier proteins. Although it has been previously reported that mRNA levels for the mitochondrial ribosomal proteins Mrp13, Mrp49, and Rml2 are induced in rho 0 cells (27,40,41), other genes such as MRP2, MRP7, MRPL16, and CYC1 had been reported to not change (26,(42)(43)(44). In our study, although all of those particular genes showed increased expression, MRPL33 and MRP20, reported to be induced in rho 0 cells (40,45), were…”
Section: Transcription Of Nuclear Genes Involved In Mitochondrial Biomentioning
confidence: 97%
“…Three proteins, L2, L16, and L27, are particularly interesting because crosslinking experiments consistently show that they make contacts with antibiotics that inhibit peptidyl transferase and with the 3' ends of tRNA bound in the A or P sites (for review, see [10]). The identities of the nuclear genes for the yeast mitochondrial r-proteins related to bacterial L2, L16, and L27 have been confirmed by gene disruption and each protein is essential for ribosomal function in vivo [13][14][15] …”
Section: Proteins Implicated In the Ptc Of The Yeast Mitochondrial Rimentioning
confidence: 96%